Management of Type IA Endoleak After EVAR by Explantation or Custom Made Fenestrated Endovascular Aortic Aneurysm Repair. (April 2021) - Doumenc, Benoit; Mesnard, Thomas; Patterson, Benjamin O.; Azzaoui, Richard; De Préville, Agathe; Haulon, Stephan; Sobocinski, Jonathan
Abstract : Objective: Proximal type 1 endoleak after endovascular abdominal aortic aneurysmal repair (EVAR) remains challenging to solve with no existing consensus. This work aims to compare two different surgical strategies to remedy type IA endoleak: endograft explantation (EXP) and aortic reconstruction or relining by custom made fenestrated EVAR (F-EVAR). Methods: A retrospective single centre analysis between 2009 and 2018 was conducted including patients treated for type IA endoleak after EVAR with either EXP or F-EVAR. The choice of surgical technique was based on morphological factors (F-EVAR eligibility), sac growth rate, emergency presentation and/or patient symptoms. Technical success, morbidity, secondary interventions, 30 day mortality, and long term survival according to Kaplan–Meier were determined for each group and compared. Results: Fifty-nine patients (91% male, mean age 79 years) underwent either EXP ( n = 26) or F-EVAR ( n = 33) during the study period. The two groups were equivalent in terms of comorbidity and age at the time of procedure. The median time from initial EVAR was 60.4 months (34–85 months), with no difference between groups. The maximum aneurysm diameter was greater in the EXP group compared with the F-EVAR group, 86 mm (65–100) and 70 mm (60–80), respectively ( p = .008). Thirty day secondary intervention (EXP: 11.5% vs. F-EVAR: 9.1%) and mortality (EXP: 3.8% vs. F-EVAR: 3.3%) rates did not differ between groups, while major adverse events at 30 days, defined by the current SVS guidelines, were lower in the F-EVAR group (2.4% vs. 13.6%; p = .016). One year survival rates were similar between the groups (EXP: 84.0% vs. F-EVAR: 86.6%). Conclusion: Open explantation and endovascular management with a fenestrated device for type IA endoleak after EVAR can be achieved in high volume centres with satisfactory results. F-EVAR is associated with decreased early morbidity. Open explantation is a relevant option because of acceptable outcomes and the limited applicability of F-EVAR.